Ciliary IFT80 balances canonical versus non-canonical hedgehog signalling for osteoblast differentiation - Xue Yuan (Nature Portfolio, 2016)
Primary cilia are highly conserved microtubule-based organelles that play essential roles in several cellular processes including osteogenesis. Here the authors show that intraflagellar protein IFT80 regulates osteoblast differentiation by balancing signalling though the canonical and non-canonical Hedgehog pathways.